The spatial spillover effect of China's outgoing audit of natural resource assets on industrial pollution: Evidence from a spatial difference-in-differences method - Shasha Huang; Chang Luo; Zunhong Zhu (Sustainable Futures)
To encourage officials to fulfill their entrusted environmental accountability, the outgoing audit of natural resources assets (OANRA) was implemented in various cities in China from 2015 to 2017. This study investigates the spatial spillover effects of the OANRA policy on industrial pollution reduction by developing spatial difference-in-differences (SDID) models. According to the findings obtained, the OANRA policy has a significant negative impact on the level and intensity of industrial wastewater and sulfur dioxide emissions. The policy has also significantly reduced the level and intensity of industrial wastewater and sulfur dioxide emissions in surrounding areas, revealing significant spatial spillover effects. But there is still significant room for improvement in effectively suppressing industrial smoke and dust. It was also found that this effect was more significant in the eastern and central regions, as well as in cities with better fiscal conditions. Finally, the impact of policy is mainly through green technological innovation, while the intermediary role of environmental governance level is not significant. The study proposed that the OANRA be used as a widespread supervision policy to combat environmental degradation. Cross-regional cooperation in the OANRA should be strengthened, and collaboration should be coordinated to promote the governance of various pollutants.